Basic Principles of Using Bank Plastic Cards and International Payment Systems in Uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
This article describes the analysis of the use, shortcomings and achievements of bank plastic cards in the Republic of Uzbekistan